Proposed A Performance Management System using KBPMS Framework in The Supply Chain OFI-Cocoa - Milla Karisma; Dermawan Wibisono; Ima Fatima (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
PT. OC - a prominent cocoa producer specializing in cocoa powder, liquor, and butter – faces challenges in its supply chain inefficiencies. Despite its established market presence, OC experiences challenges in procurement, production, inventory management, and logistics. These inefficiencies are attributed to the absence of a structured performance management system, which hinders the company’s ability to align operational activities with strategic objectives and optimize resource utilization. This research aims to address these issues by applying the Key Business Performance Management System (KBPMS) framework, which offers a comprehensive approach to identifying, measuring, and improving operational performance. The research is divided into several stages: (1) Foundation, (2) Basic Information, (3) Design Process, (4) Implementation Process, and (5) Refreshment. Primary data was collected through interviews with key stakeholders. Secondary data was gathered from internal company records and external literature. The study proposes a tailored KBPMS framework for PT. OC. Seventeen Key Performance Indicators (KPIs) were developed to monitor supply chain activities, categorized into three groups: (1) Business Results; (2) Internal Processes; and (3) Resource Capability. The results of this study highlight that a structured performance management system helps to enhance operational efficiency, reduce costs, and support sustainable business growth.